2020
DOI: 10.1155/2020/4052619
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Correlation of Skeletal Maturation Using the Stages of Dental Calcification in a Peruvian Population

Abstract: Objective. To identify the correlation between the Baccetti method of SM (skeletal maturation) and the stages of DC (dental calcification) using the Demirjian method in the Orthodontics Service of the Universidad Peruana Cayetano Heredia (UPCH) in Lima-Peru. Materials and Methods. The sample was obtained from panoramic and lateral radiographs of 200 subjects (116 women and 84 men) with ages between 9 and 17 years. Canine, premolar, and molar teeth calcification was evaluated using the Demirjian method while SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
1
0
1
Order By: Relevance
“…Various studies have employed Spearman’s correlation coefficient to establish the relationship between DI stages, skeletal maturity, 2 , 3 and PPS. 14 , 15 , 16 , 17 , 18 The results of these studies indicate a robust association between DI stages and skeletal maturation, aligning with the findings of this study. However, it’s important to note that high Pearson and Spearman’s correlation coefficients only indicate a strong relationship between the two variables and do not imply that the values ​​obtained by both methods are identical.…”
Section: Discussionsupporting
confidence: 89%
“…Various studies have employed Spearman’s correlation coefficient to establish the relationship between DI stages, skeletal maturity, 2 , 3 and PPS. 14 , 15 , 16 , 17 , 18 The results of these studies indicate a robust association between DI stages and skeletal maturation, aligning with the findings of this study. However, it’s important to note that high Pearson and Spearman’s correlation coefficients only indicate a strong relationship between the two variables and do not imply that the values ​​obtained by both methods are identical.…”
Section: Discussionsupporting
confidence: 89%
“…En Perú, existe un limitado número de estudios publicados que aplicaron el método original de Demirjian, la mayoría de ellos comparándolo con otros métodos como el de medición de ápices abiertos de Cameriere (Cameriere et al, 2007), maduración de tercer molar de Cameriere (Quispe Lizarbe et al, 2017), edad vertebral (Flores-Mir et al, 2005Mauricio-Vilchez et al, 2020) y maduración de falange media del tercer dedo (Valverde et al, 2004). Los estudios analizados sobre individuos menores de 22 años muestran resultados de ED confiable y método práctico para evaluar la maduración esquelética (Flores-Mir et al, 2005;Cameriere et al, 2007;Fonseca et al, 2015;Mauricio-Vilchez et al, 2020). Tabla I. Distribución de muestra por sexo y grupo etario.…”
Section: Discussionunclassified
“…8 The researchers have suggested that racial variation, nutrition, socioeconomic levels, and urbanization are causative factors for the dierences in this correlation. 9 Therefore, the rationale for the current study was to determine whether a signicant correlation exists between mandibular second molar calcication and the skeletal maturity indicator, i.e., cervical vertebrae maturation stages, for this sample of Pakistani subjects. No study in this population has reported this correlation in individuals with skeletal class II due to mandibular deficiency.…”
Section: Introductionmentioning
confidence: 99%